Strength and Durability Characteristics of Coconut Fibre Reinforced Earth Cement Blocks - Thanushan, K.; Yogananth, Y.; Sangeeth, P.; Gracian Coonghe, J.; Sathiparan, N. (Taylor & Francis Group, 2021)
The study investigated the improvements in post-peak resistance induced by the introduction of coconut fiber in earth cement blocks. Earth cement blocks reinforced by coconut fiber of various fiber weight fractions were tested under axial compression and flexural loading to examine the response of the material in terms of peak load-carrying capacity, post- peak residual strength and toughness. It was observed that the coconut fiber reinforcement greatly improved the residual strength, ductility and energy absorption of the earth cement blocks. For durability, against the alkaline attack and the acid attack was reduced by the addition of coconut fiber in the mortar. Similar durability improvement shows against freeze- thaw and wet-dry cycle.
Keywords: Earth cement block; Coconut fibre; Strength; Durability